Ferrous Ion Chelating Modification and Treatment of Iron-Deficiency Anemia of Exopolysaccharide from Lachnum sp. - Zong, Shuai; Wu, Yan-na; Yang, Liu; Surhio, Maheen Mahwish; Ye, Ming (Current Chemical Biology, 2016)
Background: Iron-deficiency anemia (IDA) is considered the most common nutrition deficiency worldwide, which results from inadequate iron supply for erythropoiesis. Current treatments have poor chemical stability, bioavailability and some side effects. Polysaccharides have a variety of bioactivities, while no reports focused on IDA treatment by Lachnum polysaccharide iron complex. Objective: The aim of this study was to develop a kind of Lachnum polysaccharide-iron complex, evaluate its physical properties and treatment for IDA. Method: Firstly, we prepared the Lachnum polysaccharide iron complex (LEP-1b-Fe) and verified it was chelated successfully by infrared spectroscopy. Then its iron content, in vitro dissolution test and reducibility were determined. At last, IDA mice were used to determine the therapeutic effect of Lachnum polysaccharide and its iron complex. Weight growth rate, food consumption, contents of red blood cell (RBC), hemoglobin (Hb) and serum iron (SI), total iron binding capacity (TIBC), kidney index and spleen index were tested. Results: Iron percentage content of LEP-1b-Fe was 17.04% with improved solubility and reducing power. Infrared spectroscopy showed the iron core in LEP-1b-Fe was polymerized β-FeOOH structure, and the interaction between Fe (III) and LEP-1b mainly took place on the hydroxyl groups. LEP-1b could significantly increase the weight growth rate and food consumption of IDA mice, reduce kidney index and effectively increase the content of RBC, Hb, SI and TIBC. LEP-1b-Fe with the same concentration had better therapeutic effect on IDA. Conclusion: LEP-1b-Fe is a kind of polysaccharide-iron complex with good therapeutic effect on IDA and improved physical properties.
Keywords: iron deficiency anemia